Nursing Value Analysis and Risk Evaluation of Acute Gastroenterology Diseases. (1st October 2021) - Feng, Feifei; Huang, Ciwan; Wu, Liling; Ye, Xiaomiao; Zhao, Xinkai
Abstract : In the Department of Gastroenterology, poor compliance, psychological anxiety, fear, and other reasons result in a high rate of breach of appointment. The failure rate of colonoscopy was 6.68. This paper proposes mastering the psychological characteristics of patients and implement humanistic care services to alleviate patients' psychological anxiety. The study found that telephone follow-up 2 days before diagnosis and treatment can let us know whether patients can come for examination and reduce the rate of nonappointment. Second, preoperative education can significantly reduce the degree of anxiety and improve the anxiety of patients. Third, the cleanliness of intestinal preparation before colonoscopy directly affects the results of colonoscopy. The incidence of missing flat adenomas due to inadequate intestinal preparation can be as high as 27%. In this paper, 7250 patients were analyzed, of which 4% failed to complete the examination, of which 32.7% were caused by unqualified intestinal preparation. The combination of telephone and network communication should be taken before colonoscopy to give education and guidance to patients, which is expected to improve intestinal preparation. To sum up, digestive endoscopic treatment technology is widely used to guide the nursing of patients after endoscopic treatment. The three effective schemes proposed in this paper can achieve higher patient satisfaction and improve the quality of nursing at the same time.